Solve the equation.
cosec 3x =
Answers
Answered by
0
As
![cosec \: 3x = \frac{ - 2}{ \sqrt{3} } \\ \\ 3x = {cosec}^{ - 1} ( \frac{ - 2}{ \sqrt{3} } ) \\ \\ 3x = {cosec}^{ - 1} (cosec( - \frac{\pi}{3} ) \\ \: \: because - \frac{\pi}{3} \: belongs \: to \: principal \: value \: branch \: of \: {cosec}^{ - 1} \\ \\ 3x = \frac{ - \pi}{3} \\ \\ x = \frac{ - \pi}{9} cosec \: 3x = \frac{ - 2}{ \sqrt{3} } \\ \\ 3x = {cosec}^{ - 1} ( \frac{ - 2}{ \sqrt{3} } ) \\ \\ 3x = {cosec}^{ - 1} (cosec( - \frac{\pi}{3} ) \\ \: \: because - \frac{\pi}{3} \: belongs \: to \: principal \: value \: branch \: of \: {cosec}^{ - 1} \\ \\ 3x = \frac{ - \pi}{3} \\ \\ x = \frac{ - \pi}{9}](https://tex.z-dn.net/?f=cosec+%5C%3A+3x+%3D++%5Cfrac%7B+-+2%7D%7B+%5Csqrt%7B3%7D+%7D++%5C%5C++%5C%5C++3x+%3D++%7Bcosec%7D%5E%7B+-+1%7D+%28++%5Cfrac%7B+-+2%7D%7B+%5Csqrt%7B3%7D+%7D+%29+%5C%5C++%5C%5C+3x+%3D++%7Bcosec%7D%5E%7B+-+1%7D+%28cosec%28+-++%5Cfrac%7B%5Cpi%7D%7B3%7D+%29+%5C%5C+%5C%3A++%5C%3A+because++-++%5Cfrac%7B%5Cpi%7D%7B3%7D++%5C%3A+belongs+%5C%3A+to+%5C%3A+principal+%5C%3A+value+%5C%3A+branch+%5C%3A+of+%5C%3A++%7Bcosec%7D%5E%7B+-+1%7D++%5C%5C++%5C%5C+3x+%3D++%5Cfrac%7B+-+%5Cpi%7D%7B3%7D++%5C%5C++%5C%5C+x+%3D++%5Cfrac%7B+-+%5Cpi%7D%7B9%7D+)
Similar questions